2011
DOI: 10.1590/s1807-59322011000800018
|View full text |Cite
|
Sign up to set email alerts
|

The impact of previous para-areolar incision in the upper outer quadrant of the breast on the localization of the sentinel lymph node in a canine model

Abstract: OBJECTIVES:This paper discusses the influence of a para-areolar incision in the upper outer quadrant of the breast on the location of the sentinel lymph node in a canine model.METHODS:The sentinel lymph node was marked with technetium-99, which was injected into the subareolar skin of the cranial breast. After the marker had migrated to the axilla, an arcuate para-areolar incision was performed 2 cm from the nipple in the upper outer quadrant. Patent blue dye was then injected above the upper border of the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The authors suggested that scar tissue would affect proper detection of the SLN. This limitation to SLN mapping has also been reported in some human patients …”
Section: Discussionmentioning
confidence: 68%
“…The authors suggested that scar tissue would affect proper detection of the SLN. This limitation to SLN mapping has also been reported in some human patients …”
Section: Discussionmentioning
confidence: 68%
“…Few studies have reported decreased SLN identification rate in patients where the lymphatic network was disrupted by a previous surgery 28,29 or radiotherapy 30 . Hlusko et al 31 investigated the impact of surgery on the drainage patterns from the canine brachium, demonstrating a partial agreement between preoperative and postoperative lymphoscintigraphy, and Vasques et al 32 showed that para‐areolar incision in the upper outer quadrant of the first mammary gland did not significantly interfere with SLN identification in a canine model. However, both studies were conducted on healthy dogs, and data on tumor‐bearing dogs is still lacking.…”
Section: Discussionmentioning
confidence: 99%